1997
DOI: 10.1007/s004250050076
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of phenolic compounds in leafy galls of tobacco

Abstract: The chemical composition of ethanolic and aqueous extracts from leafy galls produced after infection of Nicotiana tabacum L. plants with Rhodococcus fascians was drastically changed compared to uninfected controls. Chlorogenic acid was abundant both in uninfected and infected plants, but caffeic acid and another cinnamoyl analogue were new in leafy galls. The most pronounced product induced in leafy galls was identified as 7-O-methyl-6-O-beta-D-glucopyranosyl coumarin (7-methyl esculin). This is the first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 34 publications
(38 reference statements)
1
17
0
1
Order By: Relevance
“…Upon addition of NIP extracts, IAA secretion did not increase, suggesting that leafy-gall-specific compounds are responsible for the observed enhancement of IAA production. Previous studies have indeed shown that the composition of amino acids and phenolic compounds differs between R. fascians-infected plant tissues and uninfected plants (19,58). Our data and previous reports also indicate that bacterial gene expression and physiology are modified in the presence of LG extracts.…”
Section: Discussionsupporting
confidence: 86%
“…Upon addition of NIP extracts, IAA secretion did not increase, suggesting that leafy-gall-specific compounds are responsible for the observed enhancement of IAA production. Previous studies have indeed shown that the composition of amino acids and phenolic compounds differs between R. fascians-infected plant tissues and uninfected plants (19,58). Our data and previous reports also indicate that bacterial gene expression and physiology are modified in the presence of LG extracts.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the activation of the KNOX pathway in response to R. fascians infection might contribute to the circumvention of plant defense and the formation of local lesions in the epidermis. Indeed, accumulation of defense-related secondary metabolites (Vereecke et al, 1997;Lin et al, 2003) or extensive cell wall thickenings (de O. Manes et al, 2001(de O. Manes et al, , 2004, typical signs of strong defense responses, have not been observed upon R. fascians infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly accepted that neoplastic tissues have biochemical and physiological characteristics different from those of host plant tissues (Vereecke et al 1997;Hartley 1998;Schö nrogge et al 2000;Konno et al 2003). However, no general theory on the exact nature of these changes had emerged based on investigations in all the major groups of gall-inducer Á/host plant combinations.…”
Section: Discussionmentioning
confidence: 99%